Optimasi Dosis Pupuk Majemuk NPK dan Kalsium pada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Utama - Ramadhaini, Rizki Fauziah; ., Sudradjat; Wachjar, Ade (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThis research was aimed to evaluate the rates of NPK and calcium fertilizers for the growth of oil palm seedling at main nursery. It was conducted in IPB Experimental Station, Cikabayan, Darmaga, Bogor from December 2011 to November 2012. The two factors, NPK and calcium, were arranged in a randomized block design with three replications. The rates of NPK fertilizer (15-15-15) were 0, 115, 230 and 460 g seedling-1. The rates of calcium fertilizer were 0, 5, 10 and 20 g seedling-1. There was no interaction effect observed between NPK and calcium fertilizer. NPK fertilizer, however had the significant quadratic effect on plant height, leaf number, stem diameter and chlorophyll content. Based on morphology variables, recommended optimum rate of NPK 15-15-15 fertilizer was 333 g seedling-1 for eight months. Thus, NPK rates were 7.00, 7.00, 19.45, 59.25, 66.3, 61.55, 58.97 and 54.16 g seedling-1 from first to eight month respectively. The optimum rate of calcium fertilizer was not determined in this experiment.Keywords: NPK 15-15-15, nutrient, optimum rates, recommendation